2015
DOI: 10.1515/amm-2015-0220
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Low-Temperature Annealing On The Properties Of Ni-P Amorphous Alloys Deposited Via Electroless Plating

Abstract: Amorphous Ni-P alloys were prepared via electroless plating and annealing at 200• C at different times to obtain different microstructures. The effects of low-temperature annealing on the properties of amorphous Ni-P alloys were studied. The local atomic structure of the annealed amorphous Ni-P alloys was analyzed by calculating the atomic pair distribution function from their X-ray diffraction patterns. The results indicate that the properties of the annealed amorphous Ni-P alloys are closely related to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Consequently, at a 500 °C annealing temperature, the coating has a lower microhardness value. In addition to the annealing temperature, the annealing time also influences the structure of the coating [ 45 , 46 ]. The structure of the coating is not much affected up to 12 h of annealing time and at a 200 °C annealing temperature.…”
Section: Ni-p–ni-p Composite Coatingsmentioning
confidence: 99%
“…Consequently, at a 500 °C annealing temperature, the coating has a lower microhardness value. In addition to the annealing temperature, the annealing time also influences the structure of the coating [ 45 , 46 ]. The structure of the coating is not much affected up to 12 h of annealing time and at a 200 °C annealing temperature.…”
Section: Ni-p–ni-p Composite Coatingsmentioning
confidence: 99%
“…The hardness is reduced beyond 400°C due to the formation of lattice defects and with the coarsening of Ni 3 P particles [25]. Zhao et al investigated the effects of low temperature annealing on the properties of amorphous Ni-P alloys over different periods [26]. It was found that levels of microhardness initially decreased and then increased with annealing time.…”
Section: Heat Treatment Effectsmentioning
confidence: 99%